Cretaceous-Eocene dinoflagellate blooms of the James Ross Basin, Antarctic Peninsula - Carvalho, M. A.; Rodriguez Amenabar, Cecilia; Costa, H.; Abbate, V.; Santiago, G.
Studies conducted to date indicate that the records of fossil dinoflagellate blooms are relatively well-known. This natural phenomenon of flowering or proliferation (bloom) of algae usually occurs in response to sudden environmental or climatic changes, leading to a monospecific or few-species assemblages. Some dinoflagellate bloom events, evidenced by their cysts (dinocysts), have been recognized in Antarctica in both Cretaceous and Cenozoic strata. In this preliminary study, five blooms events are characterized, three of them identified from material collected in the James Ross Basin, Antarctic Peninsula (Cretaceous and Eocene) while the remaining two were obtained from the literature (late Maastrichtian and K/Pg boundary). In the Santa Marta Formation (lower Santonian) outcropping on James Ross Island, a bloom of Odontochitina porifera was recorded, reaching 80% of the marine assemblage (92 cysts in total). This bloom matches with the lowest values of continental-derived elements (spores, pollen grains and phytoclasts), which indicates a marine environment far from terrigenous sources. In the Snow Hill Island Formation (late Campanian - early Maastrichtian) cropping out on James Ross and Snow Hill Islands, two peaks of abundance of Impletosphaeridium clavus were identified (73% and 31% of the marine assemblage, respectively), which would have been occurred in response to cold pulses during the Cretaceous, however, without the development of sea ice cover. Likewise, the bloom of Impletosphaeridium clavus (99% of the marine association) in a section of the López de Bertodano Formation (late Maastrichtian) on Marambio Island (Seymour) was reported in the literature associated with the presence of seasonal sea ice and a stratified water column. In the same section, a bloom of different Manumiella species (68% of cysts) was recognized. This genus is characteristic of coastal and shallow-marine environments and could indicate short-term regressions and/or an oceanic cooling that occurred just before the Late ...